An Enhanced Software Framework for Improving QoS in IoT - Tomer, U.; Gandhi, P. (Engineering, Technology & Applied Science Research, 2022)
Internet of Things (IoT) and Artificial Intelligence (AI) with its subcomponents are the latest emerging technologies that make our daily lives easier. Quality of Service (QoS) plays a very important role in IoT due to the large number of interconnected nodes. QoS is inversely dependent on the node count, i.e. the increment of nodes causes hampering to QoS, as increasing the number of nodes increases the number of requests to the IoT server. An enhanced framework is strongly needed to control QoS in IoT applications. This study proposes and implements an enhanced framework using Matlab, to control the number of requests. The proposed model can improve QoS parameters like throughput, latency, and packet loss by reducing the number of requests generated by the end nodes without compromising the services to the end user. The results showed that QoS parameters improved in terms of throughput by 5-10%, packet loss by up to 6%, and packet latency by 4%. This model can also be tested in hardware and may provide a better QoS solution.